Structural diversity in (vesicular)–arbuscular mycorrhizal symbioses - SMITH, F. A.; SMITH, S. E. (The New phytologist, 1997)
summary This review describes diversity in the structure of (vesicular)‐arbuscutar (VA) mycorrhizas, i.e. endomycorrhizas formed by Glomalean fungi. In particular, we consider the extent in the plant kingdom of the two classes first described by Gallaud (1905). These are: (1) the Arum‐type, defined on the basis of an extensive intercellular phase of hyphai growth in the root cortex and development of terminal arbuscules on intracellular hyphai branches; (2) the Paris‐type, defined by the absence of the intercellular phase and presence of extensive intracellular hyphai coils. Arbuscules are intercalary structures on the coils. However, there have been many reports that in Paris‐types arbuscules are relatively few in numbers, small, or absent altogether. A survey of the literature has revealed that Paris‐types occur more frequently in the plant kingdom than Arum‐types and predominate in ferns, gymnosperms and many wild angiosperms. The cultivated herbs that are the subject of much experimental work are mostly Arum‐types. Although evidence is still limited, there are differences at the family level. In 41 angiosperm families there are records of only Poris‐type VA mycorrhizas and in 30 families records of only Arum‐types. Another 21 families have examples of both classes, or intermediates between them. Accordingly, we consider whether the original division into two classes is still useful. We conclude that it is when considering the physiology of the symbiosis and especially the issue of whether different fungus/host interfaces have specialized roles in transfer of inorganic nutrients and organic carbon between the partners, if there is no such specialization between hyphai coils and arbuscules, then the latter might not be necessary1 for the function of Paris‐types. This would account for reports of the infrequency or absence of arbuscules in this class. The control exerted on structures by the genomes of host and fungus, and possible reasons (anatomical and physiological) for the existence of the VA mycorrhizal structures, are discussed. The presence or absence of extensive intercellular spaces and differences in the wall structure of cortical cells might be particularly important in determining which type of VA mycorrhiza is formed. CONTENTS Summary 373 I. Introduction: Arum‐types and Pom‐types 374 II. Possible functional implications 375 III. Extent of the two classes in the plant kingdom 377 IV. Is the distinction between classes useful? 383 V. The structural basis 383 VI. The role of the fungal genome 384 VII. Physiology revisited 384 VIII. Conclusions 385 Acknowledgements 386 References 386